Mormon Marriage Is Also Terrestrial: An Study on Gender in Phyllis Barber’s Raw Edges: A Memoir - Chaparro Sainz, Ángel (Miscelánea: A Journal of English and American Studies, 2014)
Phyllis Barber was raised as a member of the Mormon Church. In her fiction and in her autobiographies this is an important element opening suitable realms to analyze her literature. Here I aim at analyzing her contribution to Mormon feminist tradition. In her latest autobiography, Raw Edges: A Memoir, Barber approaches marriage as an institution, helping to illustrate the relevance that certain gender roles still have within Mormon culture. Through the confession of her own failure, Barber echoes former references to penetrate into topics dealing with gender issues within Mormon culture.